Modern ecological crisis and threat of deantropologization - Matza, K. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 1970)
There are considers the demonstration of the present – day ecological crisis in the natural environment and society. The deepening process of deantropologization goes in society, i.e. losses by the man of the physical and psychical essence. By the culprit of modern ecological and anthropological crises there is a man. His universal power (intellectual, technical, production) becomes the instrument of his self-destruction simultaneously (autoecosuiside)